Tantangan Pendidik Agama Islam Di Era Society 5.0 - Muhammad Rizqi Romadlon; Aji Wibawa (Universitas Ngeri Malang, 2022)
Educators have an important role in Islamic religious education, if there are no educators the world of education will not be able to face and compete in the era of society 5.0. educators are the fulcrum for the development of students, if educators cannot educate students they cannot compete in this era of society 5.0 . Therefore the quality of students is very dependent on educators or teachers. Educators or teachers must seek various ways to create a system of teaching science and forming the character of students. This study uses research in the literature review. Data accumulation or data collection techniques the researcher himself will examine data related to the challenges of Islamic religious educators in the era of society 5.0. the data that has been obtained from e-books, journals, articles related to the problems studied will then be grouped and further analysis will be carried out, after the data analysis the researcher will draw conclusions from da The results of the research are that educators must have abilities that are able to face challenges in the era of society 5.0. At least there are several abilities that must be possessed by a teacher or educator, namely the ability to solve and find solutions to a problem, secondly the ability to think critically, the third is the ability to think creatively and innovatively. These three abilities must be owned by an educator or teacher who is expected to be able to solve a problem that will be faced in the world of Islamic religious education in the future. Pendidik memiliki peranan penting dalam pendidikan agama islam,jika tidak ada pendidik dunia pendidikan tidak akan bisa menghadapi society 5.0.pendidik adalah titik tumpuh pada perkembangan perserta didik,jika pendidik tidak dapat mendidik peserta didik tidak bisa bersaing dalam era society 5.0 ini.Oleh sebab itu kualitas dari peserta didik sangat bergantung pada pendidik atau guru.pendidik atau guru harus mengupayakan berbagai cara untuk menciptakan sistem pengajaran ilmu dan pembentukan karakter peserta didik.Penelitian ini menggunakan riset yang ada di kajian pustaka.teknik akumulasi data atau pengumpulan data itu sendiri peneliti akan mengkaji data yang berhubungan dengan tantangan pendidik agama islam di era society 5.0.data yang telah didapat dari e-book,jurna,article yang berhubungan dengan masalah tersebut selanjutnya data akan di kelompokkan dan akan dilakukan analisis lebih lanjut,setelah data dinalisis peneliti akan mengambil kesimpulan dari data yang sudah di analisis terserbut.hasil penelitiannya adalah pendidik harus mempunyai kemampuan kemampuan yang mampu untuk menghadapi tantangan tantangan di era society 5.0.setidaknya ada sebagian kemampuan yang harus dikuasai untuk seorang guru atau pendidik yaitu perama kemampuan untuk memecahkan dan menemukan solusi suatu masalah,kedua kemampuan untuk berfikir secara analitis dan refleksif,ketiga kemampuan untuk berfikir kreatif dan inovatif.ketiga kemampuan tersebut harus dimiliki seorang pendidik atau guru tersebut diharapkan bisa memecahkan suatu masalah yang akan dihadapi dalam dunia pendidikan agama islam kedepannya.